DIPLOMASI PUBLIK KOREA SELATAN TERHADAP INDONESIA: PROMOSI PARIWISATA HALAL KOREA PERIODE 2017-2021 - Nada Nur Maulidina (2023)
South Korea is a country with a non-Muslim majority population, improving Muslim-friendly facilities and diversifying markets targeting Muslim-majority countries, one of which is Indonesia. South Korea through the Korea Tourism Organization (KTO) is carrying out various public diplomacy efforts through a series of Muslim friendly tourism programs. The author analyzes using the concepts of public diplomacy and halal tourism. Descriptive qualitative research methods are used to explain public diplomacy through the Muslim friendly tourism program that has been carried out. The Korea Tourism Organization carries out public diplomacy efforts through news management, communication strategies, and building relationships which are carried out both offline and online. The results of this study indicate an increase in visits by Indonesian Muslim tourists and a positive image of the Indonesian people towards South Korea.